2019
DOI: 10.1021/acsaem.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine and Copper Codoping for High Performance Li2O-Based Cathode Utilizing Solid-State Oxygen Redox

Abstract: Transition-metal-doped Li2O cathodes using redox reaction of solid-state oxygen are candidates as high capacity cathode materials for lithium-ion batteries. In our previously reported study, copper-doped Li2O (CuDL) exhibited a high charge–discharge capacity of 300 mAh g–1. However, the developed cathode not only exhibited poor cyclability but also decomposed during charge–discharge cycles. In this study, fluorine and copper were codoped into the Li2O structure by stepwise mechanochemical reaction to create a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Given that the molar quantities of CuF 2 added in the synthesis are relatively low, 19 F very fast magic angle spinning NMR (VFMAS-NMR) was carried out to verify the presence of fluoride in the F-doped samples. 19 F VFMAS-NMR of LiF and CuF 2 was first obtained, (Figure S2), and the LiF sample exhibited a peak centered at −211.79 ppm, consistent with what has been reported by Shimada et al 25 Whereas, in the 19 F NMR spectrum of CuF 2 , two signals are observed at −212.08 ppm, associated with HF adsorbed on the surface, and at −125 ppm, attributed to impurities in the raw material (Figure S2 (a)). Further, given the paramagnetic nature of copper(II), a signal associated with F bonded to Cu in CuF 2 is not expected.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…Given that the molar quantities of CuF 2 added in the synthesis are relatively low, 19 F very fast magic angle spinning NMR (VFMAS-NMR) was carried out to verify the presence of fluoride in the F-doped samples. 19 F VFMAS-NMR of LiF and CuF 2 was first obtained, (Figure S2), and the LiF sample exhibited a peak centered at −211.79 ppm, consistent with what has been reported by Shimada et al 25 Whereas, in the 19 F NMR spectrum of CuF 2 , two signals are observed at −212.08 ppm, associated with HF adsorbed on the surface, and at −125 ppm, attributed to impurities in the raw material (Figure S2 (a)). Further, given the paramagnetic nature of copper(II), a signal associated with F bonded to Cu in CuF 2 is not expected.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…These prominent peaks are attributable to 111, 220, and 311 reflection peaks of the cubic antifluorite phase, with a lattice parameter of 4.64 Å. It may be suggested that Li 6 CoO 4 decomposes to Li 2 O and CoO; however, this XRD evidence confirms the absence of Li 2 O, given that the lattice parameter of ball-milled Li 2 O is reported to be about 4.615 Å . Co K -edge X-ray absorption near edge structure (XANES) spectra also rule out the decomposition (see Figure d,e).…”
Section: Resultsmentioning
confidence: 91%
“…It may be suggested that Li 6 CoO 4 decomposes to Li 2 O and CoO; however, this XRD evidence confirms the absence of Li 2 O, given that the lattice parameter of ball-milled Li 2 O is reported to be about 4.615 Å. 53 Co K-edge X-ray absorption near edge structure (XANES) spectra also rule out the decomposition (see Figure 1d,e). Both in the pre-edge region and in the white line of the spectrum, the trend exhibited by BM-LC matches well that of P-LC and is observed to be quite different from that of CoO.…”
Section: ■ Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, the cyclability of CuDL has been improved using fluorine doping. 57 Doping other elements such as fluorine in cationic and anionic sites potentially can enhance the cathode performances of TMDLs. In addition, the surface modification of CoDL by vinylene carbonate or fluoroethylene carbonate shows excellent capacity improvement from 270 to 450 mA h g À1 while retaining its cyclability.…”
Section: Effect Of Ni-doping To Lithium Oxidementioning
confidence: 99%